Changing outcomes of stem cell transplantation in primary immunodeficiencies: Results from a tertiary-care charitable trust hospital in Mumbai - Ambreen Pandrowala, DNB; Mukesh Desai, MD; Manisha Madkaikar, MD; Shilpa Kulkarni, MD; Lakshmi Shobhavat, DNB; Jayashree Mishra, MD; Shreepal Jain, MD; Parmarth Chandane, MD; Kunal Sehgal, MD; Saroj Chavan, DNB; Parag Karkera, MS, MCh; Pradnya Bendre, MS, MCh; et al. (Journal of Allergy and Clinical Immunology: Global, 2023)
Background: Hematopoietic stem cell transplantation in primary immunodeficiency disorders has come a long way since the first transplant in 1968. In India, pediatric stem cell transplantation long-term survival outcomes range from 62.5% to 75%, compared to 90% in high-income countries. Objective: We present single-center data of primary immunodeficiency transplants with immune-reconstitution evaluation after transplantation from a charitable trust hospital. Methods: Retrospective data of children transplanted for primary immunodeficiency disorders from March 2019 to March 2022 in a newly established transplant unit were collected. Data of pretransplant infections and comorbidities, surveillance for carbapenem-resistant Enterobacteriaceae, transplant characteristics, donor source, graft-versus-host disease, posttransplant infections, immune reconstitution, overall survival at 1 year, and immunodeficiency-free survival were collated. Results: Twenty-one patients underwent transplantation for primary immunodeficiency disorders. The median age at transplantation was 3 years and 5 months (range, 7 months to 17 years). Seventy-five percent of the cohort had organ involvement, with lung being the most common organ involved, followed by central nervous system. Fifty-two percent of children had peritransplant infections, with most of them recognized at the pretransplant assessment. Among 20 of 21 children with engraftment, 94% had complete chimerism initially, with 33% developing mixed chimerism over time. The median duration of immunosuppression was 3 months after transplantation, and only 1 child required systemic graft-versus-host disease treatment for more than a year. Immune-reconstitution showed good T-cell recovery at 3 months and naive T-cell production at 6 months. There was no regimen-related or sepsis-related mortality. Overall survival of the cohort was 95% at 1-year follow-up. Immunodeficiency-free survival was 86% after a median follow-up of 20 months. Conclusions: Immunodeficiency-free and graft-versus-host disease–free survival can be achieved in the majority of children with primary immunodeficiencies using enhanced supportive care and the latest transplantation algorithms.